PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH - Dr. Ismail Razak, M.Si.; Rasmansyah (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
The aim of this study was to analize the influence of services quality indicators on the satisfaction of customers. Primary data was obtained from customers of Bank BNI Pondok Gede Plaza, Bekasi City through admission filling of questionnaire by using scale of Likert. In this study is used purposive sampling method. Data analysis technique used in this research is simple linear regression and multiple linear regression. The results of this study indicated that tangible, reliability, responsiveness, assurance, and emphaty positively and significant influenced the satisfaction of customers. The conclution of this study is that reliability was dominant than the other service quality indicators in influencing the satisfaction of customers.